The effect of plyometric exercises on the muscular power of the lower and upper extremities and some offensive skills in basketball (Journal of the College of Basic Education, 2022)
The research included five chapters:The first chapter included the introduction and the importance of the research, as the introduction dealt with that physical education has a respectable position among the various sciences that serve the individual and society and contribute to its construction and happiness. The researcher pointed out that the use of plyometric exercises in the game of basketball is not one of the newly invented things, and despite that, interest in it has increased recently after it has become an important part of the physical preparation programs, which aims to develop the ability of the legs and arms, especially in some offensive skills (chest handling). Plump by changing direction and shooting peacefully) in the game of basketball that requires high muscle capacity